2009
DOI: 10.1093/humrep/dep020
|View full text |Cite
|
Sign up to set email alerts
|

Absence of annulus in human asthenozoospermia: Case Report†

Abstract: The annulus is a septin-based ring structure located at the junction of the midpiece (MP) and the principal piece (PP) of spermatozoa flagellum. In the mouse, deletion of Septin 4, a structural component of the sperm annulus, prevents annulus formation and leads to MP-PP disjunction, flagellar bending, asthenozoospermia and male sterility. Testis anion transporter 1 (Tat1) is a germ cell-specific member of the SLC26 anion transporter family and is co-expressed with Septin 4 at the sperm annulus. Interestingly,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
58
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 42 publications
4
58
0
5
Order By: Relevance
“…Therefore, they introduced the septins as appropriate diagnostic markers for a subset of asthenozoospermia. In France, Lhuillier and colleagues [10] in a similar study analyzed 75 cases of asthenozoospermia including 28 cases of isolated asthenozoospermia, 13 cases of oligo-asthenozoospermia and 34 cases of teratoasthenozoospermia, but they found only one case of loss of annulus that is in accordance with our finding on a population with the same ethnicity. This discrepancy may be attributed to the origin of the populations screened (Japanese versus Caucasian), to the small sizes of the cohort studies or to other causes remains to be determined.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, they introduced the septins as appropriate diagnostic markers for a subset of asthenozoospermia. In France, Lhuillier and colleagues [10] in a similar study analyzed 75 cases of asthenozoospermia including 28 cases of isolated asthenozoospermia, 13 cases of oligo-asthenozoospermia and 34 cases of teratoasthenozoospermia, but they found only one case of loss of annulus that is in accordance with our finding on a population with the same ethnicity. This discrepancy may be attributed to the origin of the populations screened (Japanese versus Caucasian), to the small sizes of the cohort studies or to other causes remains to be determined.…”
Section: Discussionsupporting
confidence: 91%
“…The annulus structure was completely absent in all spermatozoa analyzed. c Western blot analysis for septin 4 which was not detected in the gel; PC positive control Septin proteins belong to the GTPase superclass of P loop NTPases [10][11][12]. Sept4 null mice show the reproductive phenotypes similar to a subset of asthenozoospermic patients [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…In the mouse, gene targeting of Septin4, Septin12, and Tat1 lead to abnormal mitochondrial organization and tail defects [6,7,11,25]. In humans, absence of the annulus is associated with abnormal mitochondrial organization in poor-motility sperm [9]. A recent study showed that DNAJB13, which is a type II HSP40, attaches itself to the annular anlage and then recruits septins via direct interaction with SEPT4 or a SEPT4-containing septin complex for the formation of an authentic annulus in the early stage of sperm flagellum morphogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Septin4 null mice are viable; however, males are sterile because they produce immotile sperm with a defective annulus [7,8]. In humans, disorganized annulus/SEPTIN rings were identified in a subset of patients with asthenozoospermia [9,10]. SEPT12 is also a component of the sperm annulus [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation